The metal chaperone protein MtmA plays important roles in antifungal drug susceptibility in Aspergillus fumigatus - Zhai, Pengfei; Ma, Yinyan; Du, Wenlong; Lu, Ling (Frontiers in Microbiology, 2022)
Drug-resistant fungal infections are emerging as an important clinical problem. In general, antifungal resistance results from increased target expression or mutations within the target protein sequence. However, the molecular mechanisms of non-drug target mutations of antifungal resistance in fungal pathogens remain to be explored. Previous studies indicated that the metal chaperone protein Mtm1 is required for mitochondrial Sod2 activation and responses to oxidative stress in yeast and in the fungal pathogen Aspergillus fumigatus, but there is no report of MtmA-related antifungal resistance. In this study, we found that repressed expression of MtmA (only 10% expression) using a conditional promoter resulted in significantly enhanced itraconazole resistance, which was not the result of highly expressed drug targets Erg11A and Erg11B. Furthermore, we demonstrated that repressed expression of MtmA results in upregulation of a series of multidrug resistance-associated transport genes, which may cause multidrug resistance. Further mechanistic studies revealed that inhibition of MtmA expression led to abnormal activation of the calcium signaling system and prompted persistent nucleation of the calcium signaling transcription factor CrzA. Our findings suggest that the metal chaperone protein MtmA is able to negatively regulate fungal resistance via affecting calcium signaling pathway.